Glomerulonephritis and autoimmune vasculitis are independent of P2RX7 but may depend on alternative inflammasome pathways. Issue 3 (2nd May 2022) - Prendecki, Maria; McAdoo, Stephen P; Turner‐Stokes, Tabitha; Garcia‐Diaz, Ana; Orriss, Isabel; Woollard, Kevin J; Behmoaras, Jacques; Cook, H Terence; Unwin, Robert; Pusey, Charles D; Aitman, Timothy J; Tam, Frederick WK
Abstract: P2RX7, an ionotropic receptor for extracellular adenosine triphosphate (ATP), is expressed on immune cells, including macrophages, monocytes, and dendritic cells and is upregulated on nonimmune cells following injury. P2RX7 plays a role in many biological processes, including production of proinflammatory cytokines such as interleukin (IL)‐1β via the canonical inflammasome pathway. P2RX7 has been shown to be important in inflammation and fibrosis and may also play a role in autoimmunity. We have developed and phenotyped a novel P2RX7 knockout (KO) inbred rat strain and, taking advantage of the human‐resembling unique histopathological features of rat models of glomerulonephritis, we induced three models of disease: nephrotoxic nephritis, experimental autoimmune glomerulonephritis, and experimental autoimmune vasculitis. We found that deletion of P2RX7 does not protect rats from models of experimental glomerulonephritis or the development of autoimmunity. Notably, treatment with A‐438079, a P2RX7 antagonist, was equally protective in WKY WT and P2RX7 KO rats, revealing its 'off‐target' properties. We identified a novel ATP/P2RX7/K + efflux‐independent and caspase‐1/8‐dependent pathway for the production of IL‐1β in rat dendritic cells, which was absent in macrophages. Taken together, these results comprehensively establish that inflammation and autoimmunity in glomerulonephritis is independent of P2RX7 and reveals the off‐target properties of drugs previously known as selective P2RX7 antagonists. Rat mononuclear phagocytes may be able to utilise an 'alternative inflammasome' pathway to produce IL‐1β independently of P2RX7, which may account for the susceptibility of P2RX7 KO rats to inflammation and autoimmunity in glomerulonephritis. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.